A solution to the flavor problem of warped extra-dimension models - Bauer, Martin; Malm, Raoul; Neubert, Matthias (Arxiv, 2011)
A minimal solution to the flavor problem of warped extra-dimension models, i.e. the excessive mixed-chirality contribution to CP violation in K-Kbar mixing arising from Kaluza-Klein (KK) gluon exchange, is proposed. Extending the strong-interaction gauge group in the bulk by an additional SU(3), and breaking this symmetry to QCD via boundary conditions, the constraints arising from the epsilon_K parameter are significantly relaxed. As a result, KK scales M_KK ~ 2 TeV are consistent with all flavor observables without significant fine-tuning. The model predicts the existence of an extended Higgs sector featuring massive color-octet scalars and a tower of KK pseudo-axial gluon resonances, whose existence is not in conflict with recent LHC dijet bounds.
Gesehen am 11.01.2018